Pola Komunikasi Orang Tua Dan Anak Di Era Digital: Parenting Dalam Perspektif Al-Qur’an (Kajian Surah Yusuf [12]: 4-6) - Rindiani, Natasya; Razzaq, Abdur; Imron, Kristina (CENDEKIA: Jurnal Studi Keislaman, 2024)
The purpose of this research is to find out parenting in QS Yusuf: 4-6 and its relevance in line with the communication patterns of parents and their children in the digital age. This research uses a type of literature by collecting data through the main source, namely the Qur'an and supporting sources in the form of articles, reading books and the web. The data analysis technique applied is to reduce the data, then present the data and finally determine the final result of the conclusion that is in line with the research. The results of his research are that parents usually wear a bad way of communication called laissez-faire, that is, parents are reluctant to chat with their children, from the consequences of freeing their children to wear gadgets that trigger the friendship between parents and their children is stuck. They should emulate Joseph's family relationship with Ya'qub who uses an interpersonal way as well as an interactive approach. Shown by the act of openness, mutual reassurance, emotional closeness in the two, Ya'qub formed it with acts of gentle interaction, civility, obedience and respect for his father and mother, tolerance and concern for his baby. The harmony for this study is that when parents wear the communication pattern recommended in QS Yusuf 4 to 6, of course family ties become harmonious. Children become more confident to express their grievances with their parents than on social media which is vulnerable to crime. Until, all hopes to achieve a happy family in the hereafter have been realized.